2002
DOI: 10.1006/jfbi.2002.1950
|View full text |Cite
|
Sign up to set email alerts
|

Gonadal sex differentiation in Atlantic halibut

Abstract: The process of gonadal sex differentiation in 338 Atlantic halibut Hippoglossus hippoglossus larvae, ranging in size from 10 mm L S to 230 mm L F , is described histologically. Gonadal sex differentiation occurred by 38·0 mm L F , which coincided with the weaned, post-metamorphic, settled stage in the life cycle. This was a gradual process that coincided with other organogenesis in the developing larvae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
3
1
Order By: Relevance
“…3). As already shown in the majority of fish species examined, females initiated gonadal differentiation earlier than males (Chang et al, 1995;Patin˜o et al, 1996;Hendry et al, 2002). In males, the appearance of the first spermatogonia occurred c. 200 dph, and differentiation was completed by 250 dph, as in the females.…”
Section: Discussionsupporting
confidence: 62%
“…3). As already shown in the majority of fish species examined, females initiated gonadal differentiation earlier than males (Chang et al, 1995;Patin˜o et al, 1996;Hendry et al, 2002). In males, the appearance of the first spermatogonia occurred c. 200 dph, and differentiation was completed by 250 dph, as in the females.…”
Section: Discussionsupporting
confidence: 62%
“…They found that female cod appear before males, with ovarian cavities first observed at 102 days post-hatch (dph) when the fish were 27 mm long (total length, TL). This is similar to what is seen in other marine species like Atlantic halibut (Hippoglossus hippoglossus) (Hendry et al, 2002). Male cod were first positively identified (by the appearance of testis containing primary spermatogonia) at 221 dph (TL ¼ 94 mm).…”
Section: Introductionsupporting
confidence: 65%
“…In salmonids like rainbow trout (Oncorhynchus mykiss), a sensitive developmental window affecting sexual differentiation is known to occur early in the larval stage (Billard, 1992). However, in several marine fish the developmental window important for sexual differentiation occurs later, at the juvenile stage after metamorphosis (Blazquez et al, 1998;Hendry et al, 2002;Chiasson et al, 2008).…”
Section: Introductionmentioning
confidence: 96%
“…Ovarian cavity formation is an early marker of female sex differentiation in some fishes, typically preceding or occurring concurrently with the onset of meiosis (Nakamura et al 1998;Strüssman and Nakamura 2002). Its formation is indeed the earliest marker of ovarian differentiation in flatfish and grouper species (Tanaka 1987;Hendry et al 2002;Luckenbach et al 2003;Murata et al 2009), as well as the Scorpaeniform species, black rockfish (Sebastes schlegeli; Omoto et al 2010). Again, this contrasts with what we observed in sablefish, because ovarian cavity formation occasionally occurred after onset of meiosis and could easily be confused with efferent ducts of testes.…”
Section: Resultscontrasting
confidence: 83%